STATISTICS OF CYBER CRIME IN INDIA: AN OVERVIEW - Pal Kaur,, Rupinder , (International Journal of Engineering and Computer Science, 2017)
Nowadays cyber crime is the most concerning issue for all developed and developing countries ,because it harm governmental confidential data as well as people in daily life transactions. In this paper I had covered some type of cyber crime with the help of print and electronic media by quoting some current cases happened related to cyber crime. In next section , statistics of crime cases are discussed which were happened in last few years and compared crimes happened in 2012 with previous years and also discussed what type of crimes are on increase and decrease